2022
DOI: 10.1177/10690727211068106
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Self-Regulatory Responses to Positive Career Goal Discrepancies: Testing Cross-Lagged Relationships

Abstract: Researchers have assessed young people’s outcomes when they do not meet their career goals, but little is known about the consequences when they do better than expected (positive discrepancies). We (a) tested the cross-lagged relationships between positive career goal discrepancies and the career-related outcomes of upward goal revision, career exploration, and career coasting, and (b) assessed the indirect relationships between positive career goal discrepancy and outcomes through self-efficacy and outcome ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…While both self- and other-referenced discrepancies are important in young ‘adults’ career development, past studies have examined self- (Akmal et al, 2022; Creed et al, 2015; Praskova & McPeake, 2021) and other-referenced discrepancies (e.g. with parents and peers; Budjanovcanin et al, 2019; Li et al, 2015) separately.…”
Section: Career Goal Discrepancymentioning
confidence: 99%
See 1 more Smart Citation
“…While both self- and other-referenced discrepancies are important in young ‘adults’ career development, past studies have examined self- (Akmal et al, 2022; Creed et al, 2015; Praskova & McPeake, 2021) and other-referenced discrepancies (e.g. with parents and peers; Budjanovcanin et al, 2019; Li et al, 2015) separately.…”
Section: Career Goal Discrepancymentioning
confidence: 99%
“…When young people appraise a career goal discrepancy, they experience a range of behavioural outcomes. These include lowered expectations, downward goal adjustment, and goal disengagement when discrepancies are negative (Creed et al, 2015, 2017; Hu et al, 2017), and upward goal revision when discrepancies are positive (Akmal et al, 2022). Past research found that career distress, which includes negative emotions of depression, anxiety, and despair (Creed et al, 2015), helped explain the relationships between negative career discrepancy and goal assimilation and goal accommodation, although a full explanation for what drives career goal adjustment in response to career-related discrepancy is yet to be clarified (Praskova & McPeake, 2021).…”
mentioning
confidence: 99%